"Gay in the Bank, Queer in the Streets": The Intersection of LGBTQQ and Social Class Identities. Issue Volume 10:Issues 1(2016) (2nd January 2016) - Burnes, Theodore R.; Singh, Anneliese A.
Abstract : Calls from the counseling literature have highlighted a need for the examination of intersections between marginalized identities and identities of social class. This article investigates the intersection of lesbian, gay, bisexual, transgender, queer, questioning (LGBTQQ) identity and social class. The authors review current literature and scholarship on these intersections, identify key issues between the intersection of these two identities, and discuss critical strategies for counselors to engage with the intersection of social class and LGBTQQ identities. Recommendations for counseling research, training, practice, and advocacy are discussed.